1993
DOI: 10.1002/j.1550-8528.1993.tb00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Obesity

Abstract: This paper reviews succinctly the evidence for a role of regular exercise in the prevention and the treatment of obesity and of its metabolic complications. Seventeen propositions relevant to an understanding of the topic are considered. The evidence suggests that regular exercise can be an important factor in the development of sustained negative energy balance conditions provided the volume of activity is high. This implies a program of low to moderate intensity exercise performed on an almost daily basis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
1
7

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(97 citation statements)
references
References 109 publications
3
86
1
7
Order By: Relevance
“…In contrast to men for whom intra-abdominal obesity is readily reduced by physical exercise, 43,44 women appear to require a substantial loss of total and subcutaneous body fat before they diminish their visceral fat stores. 45 Previous cross-sectional studies of white populations found that leisure-time physical activity was associated with smaller decrements in the WHR among women than among men.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to men for whom intra-abdominal obesity is readily reduced by physical exercise, 43,44 women appear to require a substantial loss of total and subcutaneous body fat before they diminish their visceral fat stores. 45 Previous cross-sectional studies of white populations found that leisure-time physical activity was associated with smaller decrements in the WHR among women than among men.…”
Section: Discussionmentioning
confidence: 94%
“…For example, high BMI has been associated with subsequent physical inactivity. 31 However, although people who are obese are usually inactive, 32 body composition, in terms of percentage body fat, is not a powerful predictor of PA habits. 30 In an intervention, baseline BMI was not significantly related to changes in step number.…”
Section: Discussionmentioning
confidence: 99%
“…3 Current weight loss recommendations advise decreasing caloric intake and increasing physical activity to generate an overall negative energy balance and are based on extensive research demonstrating the independent benefits of both behaviors on weight control. [4][5][6] What emphasis to place on diet vs physical activity in addressing clinical and public health needs has not been resolved and invites the question of which behavioral change or combination of behavioral changes is most effective and realistic. Assessment of the relative benefits of dietary changes and increased exercise on weight loss are largely based on comparisons between program types and would suggest that dietary changes are more effective.…”
Section: Introductionmentioning
confidence: 99%